3-Hydroxy-2-methylpropylglucosinolate and other glucosinolates from Reseda luteola (Resedaceae) - Nicola, Gina Rosalinda de; Zhu, Jianzhong; Pattison, David I.; Koch, Marcus; Staerk, Dan; Agerbirk, Niels (Biochemical systematics and ecology, 2024)
We identified 3-hydroxy-2-methylpropylglucosinolate in foliage of Reseda luteola L, although the side chain stereochemistry was not resolved. The glucosinolates (GSLs) in R. luteola extracts were bound to an anion exchange column and enzymatically desulfated, followed by isolation by preparative HPLC of the desulfo derivatives, the structures of which were elucidated by NMR and/or MS/MS. Presence of intact 3-hydroxy-2-methylpropylGSL in extracts was supported by direct LC-MS detection and MS2 loss of HSO4−. Prominent GSLs in R. luteola foliage were 3-hydroxy-2-methylpropylGSL as well as the previously known indol-3-ylmethylGSL and the 2R (minor) and 2S (major) isomers of 2-hydroxy-2-phenylethylGSL. Minor GSLs included the expected biosynthetic precursors 2-methylpropylGSL (tentative) and phenethylGSL, as well as 1-methylpropylGSL (tentative) and benzylGSL. The 3-hydroxy-2-methylpropylGSL matched a previously reported but so far unidentified constituent in Limnanthes alba (Limnanthaceae). The identity of investigated R. luteola was confirmed morphologically and from DNA barcoding, and a Reseda phylogeny was constructed. In conclusion, 3-hydroxy-2-methylpropylGSL occurs in at least two basal families of the Brassicales order.
Gesehen am 05.03.2025